Mapping Radical Islam in Indonesia - Jamhari Jamhari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2003)
This paper focuses on the emergence of groups that, according to their followers, want to apply Islamic teachings comprehensively (kaffah) and wholeheartedly. These groups have been variously described as fundamentalist, extremist, radical, and militant. Of course, they do not apply these labels to themselves. The labeling of certain groups has resulted in them gaining negative or pejorative images. It is important to note that the label